Influence of Surface Treatment on Steel Adhesive Joints Strength—Varnish Coats - Anna Rudawska (MDPI AG, 2021)
The purpose of the paper is to determine the impact of surface treatment on the strength of adhesive joints, made from various steel sheets. Two variants of the surface treatment steel adherends were used: without the varnish coat and with the varnish coat, using three polymer-based varnishes (a simple, a hybrid, and a gel). Two types of the adhesives were used to prepare the adhesive joints: a single-component cyanoacrylate adhesive and a two-component epoxy adhesive. A strength test of the adhesive joints (EN DIN 1465 standard), a coating adhesion test (ASTM D3359-B standard), and surface topography, as well as surface roughness, parameters (PN-EN ISO 11562, PN-EN ISO 4287, and PN-EN ISO 25178 standards) were used. Based on the strength tests, it was observed that the adhesive joints, with the hybrid varnish onto the adherend’s surface, achieved markedly lower shear strength. The best results, in terms of the adhesive joint strength, made using the cyanoacrylate adhesive were achieved for the joints where the adherends were coated with a simple varnish, while in the joints made using the epoxy adhesive, the highest shear strength was achieved by the joints of sheets whose surfaces were coated with the gel varnish.